A teacher’s experience in enacting the knowledge-building approach to teaching about climate change - Azmath, Fathimath; Tee, Meng Yew (Frontiers in Education, 2026)
This study investigates how a science teacher in a Maldivian secondary school enacted the Knowledge Building (KB) approach to facilitate student learning about climate change. A qualitative case study design was used. Data were collected through classroom observations, interviews, and analysis of artefacts generated during lessons, including digital KB platforms such as Padlet. The findings reveal that the teacher initially navigated significant uncertainty and low self-efficacy due to her unfamiliarity with knowledge-building pedagogy, which constrained her ability to facilitate inquiry and support idea improvement. Through sustained reflective practice and self-directed professional learning, she gradually redefined her role, shifting from a knowledge transmitter to a facilitator who valued student ideas, promoted epistemic agency, and encouraged independent learning. The study offers implications for professional development, suggesting that teachers require sustained support, modelling, and scaffolding to integrate knowledge-building approaches when addressing complex, real-world problems such as climate change.